Enhancing Coffee Productivity and Carbon Stock in Agroforestry Systems Using the WaNuLCAS Model under Climate Change - Nurwarsito, Heru; Suprayogo, Didik; Prayogo, Cahyo; Fitra, Ahmad Ali Yuddin (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2025)
The coffee-pine agroforestry model, where coffee is grown under shade trees, provides environmental benefits such as carbon sequestration and soil health improvement. However, maintaining carbon stocks over time is challenging due to climate change, which alters water and nutrient availability. Using the WaNuLCAS model, this study assessed system optimization under various climate scenarios, focusing on coffee yield, carbon stock, and biomass balance. The model simulates water and nitrogen cycling as well as coffee–pine interactions. The results showed that an increase in rainy season enhanced coffee growth, while applying Best Management Practice (BMP) led to a 44.64% higher coffee yield and a 4.52% increase in biomass production compared with the control. Conversely, low coffee (LC) with poor management increased carbon stock by 6.91% and biomass by 26.74%, the largest differences observed between treatments. This highlights trade-offs in land use performance. Previous studies mainly emphasized agroforestry’s contributions to carbon sequestration, biodiversity, and timber, with limited quantification of trade-offs between yield, carbon, and biomass under varying rainfall. By integrating site-specific calibration of the WaNuLCAS model, this study offers a novel approach showing how contrasting strategies (BMP vs. LC) differently optimize productivity and ecological services, guiding climate-resilient coffee agroforestry.